Legal Provisions in Indonesia Submitting a Guardianship Application to the Court After the Birth of Law Number 29 of 2019 - Ferry Susanto Limbong; Aisyah Aisyah (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This study aims to find out about the Provisions for Submission of Applications for Guardianship After the Birth of the Government Regulation of the Republic of Indonesia Number 29 of 2019. The method used in writing this journal is the Qualitative Method with data collection techniques, namely library research which is collected and analyzed using descriptive techniques. Based on the results of the research, it shows that the provisions for child guardianship have been strictly regulated based on the Government Regulation of the Republic of Indonesia Number 29 of 2019 which states that a guardian is a person or entity that in reality exercises parental authority over a child. Furthermore, Article 1 paragraph 2 states that parents are biological fathers and/or mothers, or fathers and/or stepmothers, or adoptive fathers and/or mothers. Furthermore, Article 1 paragraph 3 states that a child is someone who is not yet (eighteen) years old, including a child who is still in the womb. Legal Procedures for Application for Guardianship After the Birth of Government Regulation of the Republic of Indonesia Number 29 of 2019 must meet the requirements as stipulated in the Government Regulation and be submitted by a person or legal entity as a potential guardian to the court. The application for the appointment of a guardian as referred to in paragraph (1) is submitted together with the application for the revocation of the guardianship. The application for the appointment of a guardian and the application for the revocation of custody which has been accepted by the Court shall be determined through trial. A person or legal entity is declared a guardian after obtaining a court order.